Pengaruh Pemberian Infused Water Lemon untuk Mengurangi Mual Muntah pada Ibu Hamil Trimester 1 - Indah Lestari; Mudy Oktiningrum; Nella Vallen Ika Puspita (Pusat Riset dan Inovasi Nasional, 2025)
Nausea and moting affect most women in early pregnancy. Up to 80% of women experience nausea and vomiting to some degree during the first trimester, and for some, these symptoms typically resolve by 12 to 14 weeks. Nausea and vomiting can occur due to elevated levels of estrogen and HCG (human chorionic gonadotropin),but psychological factors also play a role in this condition. Complaints of nausea and vomiting are physiological in nature; however, if not promptly addressed, they can turn pathological and lead to pregnancy complications. Non-pharmacological methods, such as lemon-infused water, can effectively tackle nausea and vomiting. This quantitative research determined the effect of lemon-infused water on relieving nausea and vomiting in pregnant women during the first trimester with a pre-experimental design and a one-group pretest-posttest design. The population of this study consists of pregnant women in their first trimester suffering from nausea and vomiting at the Kedungmundu Public Health Center. The chosen sampling technique was purposive sampling yielded a sample size of 30 pregnant women in their first trimester. The Wilcoxon statistical test and the result show a p-value of 0.000 (p<0.05), accepting the alternative hypothesis (Ha) and rejecting the null hypothesis (Ho). This indicates that giving pregnancy women lemon-infused water relieves nausea and vomiting during the first trimester.